Yield of irrigated cool-season grasses in southwestern Kansas - Hale, R.L.; Thompson, C.T.; Hampton, M.; Gold, G.L.; Dumler, Troy J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nine varieties and a commercial mix of perennial cool-season grasses were planted in four replicated plots in two counties in southwestern Kansas to evaluate yield and adaptability when produced under irrigation. The varieties were smooth bromegrass, ‘Slate’ intermediate and ‘Hycrest’ crested wheatgrass, ‘Kentucky 31’ and ‘Max-Q®’ tall fescue, ‘Profile’ orchardgrass, ‘Hykor’ festulolium, and ‘Dixon®’ and ‘Lakota®’ matua grass. The mix was Sharp Brothers’ ‘Pasture Mix #6®’, a blend of smooth bromegrass, ‘Regar’ meadow bromegrass, Slate, Profile, and ‘Garrison’ creeping foxtail. Grasses were planted in September 2002. Forage samples were collected in the spring and fall of 2003 and 2004 to measure dry matter content and yield. Fall 2003 samples were not collected at Stevens County because calves grazed them. The greatest grazing preference was for orchardgrass. The least preferred was crested wheatgrass. Spring cuttings yielded less forage than expected in Ford County in 2004 and in Stevens in both years due to dry winters and higher than normal spring temperatures in 2004. Annual dry matter yields ranged from 10,565 to 13,694 lb per acre in Ford County during 2003, 5661 to 9032 lb per acre in Ford in 2004, and 6189 to 14,552 lb per acre in Stevens County in 2004. The consistently highest-producing grasses for both years were the fescues, intermediate wheatgrass, orchardgrass, and the pasture mix. The matuas had high yields in Ford County during 2003, but winter kill reduced the other spring yields. However, new grass plants from a high 2003 and 2004 seed production improved fall 2004 matua yields. The overall lowest-producing grass was crested wheatgrass.
Keywords: Beef; Irrigated cool-season grasses; SW Kansas